Competing paradigms of flood management in the Scottish/English borderlands. Issue 3 (6th June 2016) - Cook, Brian; Forrester, John; Bracken, Louise; Spray, Christopher; Oughton, Elizabeth
Abstract : Purpose: – The purpose of this paper is to explore how flood management practitioners rationalise the emergence of sustainable flood management. Key to this analysis are differences rooted in assumptions over what flood management is and should do. Design/methodology/approach: – The popularity of natural flood management offers a case with which to explore how a dominant framing persists and how individuals at the government-public interface negotiate different visions of future flood management. The authors draw on the perceptions of flood experts, elucidating a deep hold amongst a professional community "grounded" in science and economics, but also their desire to innovate and become more open to innovative practices. Findings: – The authors show how the idea of "sustainable" and "natural" flood management are understood by those doing flood management, which is with reference to pre-existing technical practices. Research limitations/implications: – This paper explores the views of expert decision making, which suffers from challenges associated with small sample size. As such, the findings must be tempered, but with recognition for the influence of a small group of individuals who determine the nature of flood management in Scotland. Practical implications: – The authors conclude that, in the context of this study, a technical framing persists by predetermining the criteria by which innovative techniques are judged. Originality/value: – Broadly, these findings contribute to debates over the evolution of flood management regimes. This recognises the importance of events while also emphasising the preparations that shape the context and norms of the flood management community between events.